Семь признаков счастья: сборник рассказов / Олег Рой - Рой Олег (Капризы и странности судьбы, 2017)
Экземпляры: ЧЗ (20181129) / Инвентарный номер: 46421 / Цена: 145 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Р 65 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44